Putting off pests - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Stemborers can cause immense damage to maize and sorghum: in some cases losses as high as 80% have been recorded, especially with one particularly damaging species, Chilo partellus. Stemborers are difficult to control by chemical means because of...